Presence of Microplastic in Bottom Sediments of the Bach Hac River in Phu Tho Province, Vietnam - Tuan Manh, Duong; Xuan Thanh Thao, Le; Duc Long, Huynh; Thi Linh, Thai; Van Manh, Do (VNU Journal of Science: Earth and Environmental Sciences, 2024)
Microplastic pollution has been one of the alarming environmental problems globally due to its widespread distribution and potential health risks. Rivers are considered one of the main pathways for microplastics receiving and transporting from land to the oceans. Furthermore, sedimentary environments are considered the main reservoirs of microplastics in the aquatic environments. This study was conducted to evaluate the distribution of microplastics in bottom sediment samples collected at Bach Hac River, Phu Tho, Vietnam. Visual verification and chemical identification of microplastics were performed using a μFT-IR spectrometer using a Nicolet iN10 MX Infrared Imaging Microscope. The results found microplastics present in all sediment samples. The concentrations of microplastics detected were in the range of 798.08 – 1454.3 microplastics/kg of dry sediment. The most detected major polymer type was Polyethylene Terephthalate (PET), accounting for 60% of the total polymers found. The most common shape of detected microplastic was fragments (72.02%). Most of the detected microplastics were small in size (20- 150 µm), accounting for 81.80%. The findings from this research could contribute to the database about microplastic pollution in Vietnam and toward the assessment of the potential ecological impacts of microplastics. Keywords: Microplastics , Polymers, Sediment, μFT-IR spectroscopy.